EFEKTIFITAS RELAKSASI AFIRMASI YOGA DALAM LAYANAN HOMECARE TERHADAP KUALITAS HIDUP IBU POSTPARTUM - Anggraeni, Ni Putu Dian Ayu; Murni, Ni Nengah Arini; Wahyuni, I Gusti Ayu Putu Sri (POLTEKKES KEMENKES SEMARANG, 2025)
During the postpartum period, mothers undergo physiological and psychological changes that require adaptation to accelerate recovery. One approach to support this process is through homecare services combined with physical activities such as yoga affirmation relaxation. This study aims to analyze the effectiveness of yoga affirmation relaxation on the quality of life of postpartum mothers. The research used a quasi-experimental design with a pre- and post-test control group approach. The study population consisted of postpartum mothers who gave birth vaginally. Using purposive sampling based on inclusion criteria, 30 participants were assigned to each group (intervention and control). The intervention was administered from day 4 to day 42 postpartum, with 30-minute sessions conducted during three home visits. Quality of life was assessed using the SF-36 questionnaire. The results showed that the intervention group experienced a greater increase in quality of life scores compared to the control group. Four out of eight quality of life dimensions showed significant improvement (p 0.05), including vitality, mental health, pain, and general health. Yoga affirmation relaxation proved effective in enhancing both physical and mental well-being. These findings support its inclusion in postpartum care to improve maternal quality of life.